What Academic Factors Influence Satisfaction With Clinical Practice in Nursing Students? Regressions vs. fsQCA - Fernández-García, David; Giménez-Espert, María Del Carmen; Castellano-Rioja, Elena; Prado-Gascó, Vicente (Frontiers in Psychology, 2020)
Clinical practices are considered one of the cornerstones in nurses' education. This study provides a framework to determine how factors in the academic environment, influence nursing student's satisfaction with their practices. A cross-sectional analytical study was conducted in a convenience sample of 574 nursing students at a private university in Valencia, during the 2016/2017 academic year, 79% (456) were women. Two statistical methodologies were used for data analysis: hierarchical regression models (HRM) and fuzzy sets qualitative comparative analysis (fsQCA). The HRM indicate that the students' mean score influences all dimensions of satisfaction. Furthermore, in the fsQCA, the type of service and center, as well as the type of management, the preference in the choice of the practice center and the number of students per period per clinical educator influence satisfaction with clinical practices. These results could be used to understand how academic factors influence nursing students' satisfaction with their clinical practices and to create intervention programmes that improve it. This will help prepare students to be the future nursing workforce.